Sir Robert Peel : statesmanship, power and party - Evans, Eric J., 1945- (Lancaster pamphlets., 2006)
Eric Evans presents an introduction to the life and career of British Prime Minister, Sir Robert Peel. The author reassesses Peel's career, arguing that although his executive and administrative strengths were great, he presented political problems which he was incapable of solving.